‘Direct’ or ‘indirect’ rule? Reconsidering the roles of appointed chiefs and native employees in Portuguese West Africa - Havik, Philip (Africana Studia, 2020)
The appointment of chiefs by colonial administrations in Africa has become a richly textured issue of debate over the last decades. While the role of native authorities has been the main focus of this debate, above all in the context of concepts such as ‘indirect’ and ‘direct rule’, it also highlighted the great variety of political, social and cultural contexts across the continent. Despite the great differences between colonial governance and practice, and the geography, demography and history of the territories involved, scholarly work has been able to draw many parallels. One of the most notable features of colonial regimes that have received much less attention is that of native employees such as clerks, guards, interpreters and liaison personnel, that exercised functions on the ‘lower’ echelons of administration. The emphasis on appointed chiefs thus needs to be balanced by a complementary focus on these employees, in order to better comprehend the inner and local workings of colonial ‘systems’. The implementation of tasks attributed to clerks and guards within the different administrative hierarchies was crucial to the maintenance and survival of the ‘system’ latter, and indeed much greater than has so far been acknowledged, for having been closest to the populations, their compatriots, under ‘their’ jurisdiction. Given their relevance, both in a numerical and qualitative sense, an analysis needs to take into account the legal and administrative procedures that affected them, but also the way they interacted within the triangular relations between administration, local chiefs and the population at large. Clerks and guards played a key role not only in the maintenance of the colonial order and as intermediaries between the administration and native dignitaries, but also in the implementation of ‘native affairs’ policies, censuses, tax collection, fines, labour recruitment drives and the gathering of information of local communities. In order to focus on some of the lesser known aspects of colonial rule and the roles of Africans in it, the present paper takes a closer look at the situation as it evolved in a Portuguese colony, i.e. Guinea, between the 1920s and the 1950s. The analysis of their roles in administration is placed in the context of the broader, ongoing debate on native employees in sub-Saharan Africa. Keywords: colonial administration, native chiefs, African employees, native affairs, taxation, West Africa, Guinea.